2023
DOI: 10.17843/rpmesp.2023.401.11205
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre los síntomas de la infección por la COVID-19 y los resultados materno-perinatales adversos en gestantes de un hospital de referencia

Abstract: Objetivos. Determinar la asociación entre los síntomas de la infección por la COVID-19 y los resultados materno-perinatales adversos en gestantes de un hospital de referencia. Materiales y métodos. Estudio transversalanalítico en gestantes en el tercer trimestre, hospitalizadas por la COVID-19 en el área de ginecología y obstetricia de un hospital general de Lima, en el 2020. Se recogieron variables clínicas y obstétricas. Para el análisis descriptivo se empleó la prueba exacta de Fisher y Chi Cuadrado, y para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Similarly, a systematic review of 62 studies, mostly cohorts, reported that patients with severe COVID-19 were at increased risk of developing gestational diabetes, preeclampsia, PROM (including PPROM), intrauterine growth restriction, fetal distress and placental abruption 18 . In Peru, a study with similar results showed that the presence of symptoms of COVID-19 infection led to an increased risk of maternal complications as a composite variable, including PPROM, which was present in 25.9% of symptomatic cases and in only 9.5% of asymptomatic cases 19 . Despite these similarities, this study specifically evaluates the association of PPROM, as a single variable, with all degrees of severity of infection, not only severe cases, which constitutes a contribution to the knowledge of this subject.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Similarly, a systematic review of 62 studies, mostly cohorts, reported that patients with severe COVID-19 were at increased risk of developing gestational diabetes, preeclampsia, PROM (including PPROM), intrauterine growth restriction, fetal distress and placental abruption 18 . In Peru, a study with similar results showed that the presence of symptoms of COVID-19 infection led to an increased risk of maternal complications as a composite variable, including PPROM, which was present in 25.9% of symptomatic cases and in only 9.5% of asymptomatic cases 19 . Despite these similarities, this study specifically evaluates the association of PPROM, as a single variable, with all degrees of severity of infection, not only severe cases, which constitutes a contribution to the knowledge of this subject.…”
Section: Discussionmentioning
confidence: 78%
“…De igual manera, en una revisión sistemática de 62 estudios, en su mayoría de cohortes, se encontró que aquellas pacientes con la COVID-19 severa tuvieron mayor riesgo de desarrollar diabetes gestacional, preeclampsia, RPM (incluida RPMP), restricción de crecimiento intrauterino, distrés fetal y desprendimiento prematuro de placenta 18 . En Perú, una investigación con resultados similares encontró que la presencia de síntomas de infección por COVID-19 llevó a un riesgo aumentado de complicaciones maternas como variable compuesta, que incluyó la RPMP, que estuvo presente en 25,9% de casos sintomáticos y solo en 9,5% de asintomáticos 19 . A pesar de estas semejanzas, este estudio evalúa específicamente la asociación de la RPMP, como variable única, con todos los grados de severidad de la infección, no solo los casos severos, lo que constituye un aporte al conocimiento de este tema.…”
Section: Discussionunclassified
See 2 more Smart Citations